Reframing Public Policy on Narcotic Case Dismissals: Integrating Maqasid al-Shari‘ah and Restorative Justice in the Contemporary Era - Waris, Irwan; Susanti, Ani; Haryono, Dandan; Rahmat Ramadhan, Bayu; Nur Akifa, Sri (MILRev: Metro Islamic Law Review, 2025)
The handling of narcotics crimes in Indonesia remains a persistent legal and social challenge, especially in balancing punitive measures with rehabilitation efforts. This empirical legal research investigates the implementation of prosecution termination policies using a restorative justice approach in narcotics cases and analyzes their compatibility with the principles of Maqasid al-Shari‘ah. Field data were collected through in-depth interviews with 12 key informants, consisting of prosecutors, judges, police investigators, religious leaders, and former drug offenders who had undergone restorative justice proceedings. Additional data were obtained through direct observation of mediation sessions at the prosecutor’s office and the analysis of legal documents, including case files and institutional guidelines. The field findings reveal that the application of restorative justice is still limited and discretionary, often depending on the initiative of individual prosecutors and the willingness of victims or communities to engage in non-litigation settlement. While some prosecutors have successfully used this approach for first-time or non-distributor offenders, significant legal and structural constraints remain—such as the absence of detailed operational guidelines, lack of coordination between institutions, and limited public understanding of restorative mechanisms. Nevertheless, the study finds that the use of restorative justice aligns substantively with the goals of Maqasid al-Shari‘ah, particularly in protecting life (hifz al-nafs), intellect (hifz al-‘aql), and religion (hifz al-din), by prioritizing rehabilitation, mental health recovery, and spiritual reintegration over mere incarceration. Restorative practices, such as sulh (mediation) and community involvement, are also consistent with Islamic legal traditions emphasizing compassion, reconciliation, and prevention of greater harm (dar’ al-mafasid). The academic contribution of this study lies in offering a normative-empirical synthesis between Islamic legal principles and restorative justice practices, providing a conceptual and policy framework for the transformation of narcotics prosecution models in Indonesia. It emphasizes the importance of integrating maqāṣid-based reasoning into contemporary criminal justice reform to foster a more humane, rehabilitative, and socially responsive legal system.